Multi-Level Complex Tasks in the System of Assessment Tools (On Example of a Physics Course) - Plotnikova, Olga Vasilevna (Razvitie obrazovaniâ (Online), 2020)
The article discusses the problem of forming a system of assessment tools in the context of modular competence-based learning. The aim of the research is to find the optimal means for assessing the level of competence formation. In author’s opinion, one of the abovementioned means is complex tasks that include several multi-level components. Based on the analysis of ways to solve this problem, presented in the scientific and pedagogical literature, the author offers criteria for selecting tasks for the formation of a system of assessment tools aimed at diagnosing the level of formation of necessary competencies, shows the role of complex tasks for such diagnostics. Using the example of the physics course, their possible structure and the problems solved by individual elements of this structure are reviewed. Examples of such tasks are given, and it is shown that they allow to diagnose the level of formation of individual elements of competence, adjust teaching methods and motivate students to work actively, seek out additional information, promote awareness of the importance of discipline as a professional one. The results of the research generalize the personal experience of teaching physics at the Far Eastern Federal University and can be used by university teachers in creating their own system of assessment tools.